A short review of Nanomaterials: Synthesis methods, properties, and applications - ALHAMAD, Ali ALNAZZA . ZEGHOUD, Soumeia .Ilham ,BEN AMOR.ZAATER,Abdelmalek . BEN AMOR,Asma. AOUADI,Abdelatif . HEMMAMI, Amira.NLEONU,Emmanuel CHILE (University of Eloued جامعة الوادي, 2023)
Due to their significant features, engineered nanomaterials have received much attention recently, sparking significant technical and monetary growth across various industrial sectors. Moreover, it is anticipated that nanomaterials will support a variety of industries, including microelectronics, materials, textiles, energy, healthcare, and cosmetics. Nanotechnology applications will lead to the development of lighter, stronger, and cleaner materials, intelligent medications, and diagnostics in the medical field. The relative hazards of various nanomaterials to humans and the environment are still up for debate, therefore, it's essential to be aware of the concerns related to possible toxicity and exposure route. Here, we go through several elements of creating, characterizing, and using nanoparticles.
Article
Keywords: Nanomaterials; Synthesis; Applications